Penerapan Hukum Islam pada Masa Rasulullah SAW sebagai Fondasi Perubahan Sosial dan Peradaban Masyarakat Jahiliyah - Tukijo (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to thoroughly examine the role of Islamic law implemented by the Prophet Muhammad (peace be upon him) in shaping a new civilization for the pre-Islamic Arab society known as the Jahiliyyah era. Employing a qualitative descriptive approach, this research analyzes primary sources such as the Qur’an and Hadith, supplemented by relevant historical literature and scholarly studies. The findings reveal that the application of Islamic law had a transformative impact on the social structure, legal order, and moral-ethical values of that society. The enforcement of criminal, civil, and family law not only established justice but also eradicated detrimental social practices such as gender discrimination, violence, and intertribal conflicts. Furthermore, Islamic law functioned as a tool for cultivating a more civilized, equitable society that upholds individual rights. This study emphasizes that the implementation of Islamic law by the Prophet was not merely a form of social regulation but a fundamental foundation for building an Islamic civilization whose influence persists to the present day.